Some Properties of Harmonic Univalent Functions in a Conic Domain.: Some Properties of Harmonic Univalent Functions - Bukhari, Syed Zakar Hussain; Ahmad, Qadeer (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
We investigate a new subclass of harmonic functions satisfying condition: Whereand.We also determine the coefficients inequalities, growth and distortion bounds, radius of star likeness for the analytic part of the harmonic functions . For specific values of parameters involved, our findings may be related to the previously known results.